RMIT University at TREC 2004 - von Billerbeck, Bodo; Cannane, Adam; Chattaraj, Abhijit; Lester, Nicholas; Webber, William; Williams, Hugh E.; Yiannis, John; Zobel, Justin (Proceedings Text Retrieval Conference (TREC), 2004)
RMIT University participated in two tracks at TREC 2004: Terabyte and Genomics, both for the first time. This paper describes the techniques we applied and our experiments in both tracks, and discusses the results of the genomics track runs; the terabyte track results are unavailable at the time of manuscript submission. We also describe our new zettair search engine, in use for the first time at TREC.